A Model for Architecture Centric Development of Automated External Defibrillators - Gurjão, Edmar C.; Barbosa, Paulo; Medeiros, Yang; Albornoz, Leo (Anais do Simpósio Brasileiro de Engenharia de Sistemas Computacionais (SBESC), 2015)
Due to complex safety requirements, medical devices must obey rigorous standards. In the development of these devices, modeling techniques must be used to analyze the design decisions in agreement with such standards. In this paper, we present a Matlab/Simulink specification as an analytical model for Automated External Defibrillators (AEDs) and its integration with a Model Based Systems Engineering (MBSE) approach through descriptive models. The proposed model allows us to analyze algorithms for decision of shock application, performance of circuits when obtaining the required voltage, safety of the produced energy for shock delivery and characteristics of signals produced at the output of the AED. The model is composed of modules with interfaces specification, allowing safe module replacement and the assessment of the module influence over the system at a technical level.